(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To determine the prevalence of overweight and obesity among children 24-72 months in Thai Nguyen city in 2021. Research subjects: 24-72 months children at Kindergartens in Thai Nguyen city in 2021. Research method: Cross-sectional description with 1203 children in kindergartens in Thai Nguyen city and determination of overweight/obesity according to WHO. Results: The overweight and obesity rate of kindergartens children in Thai Nguyen city was 15.4%, the overweight rate was 8.1% and the obesity rate was 7.3%; The ratio of overweight and obesity in urban areas is higher than in suburban areas (13.0% vs. 2.4%, p<0.001); The prevalence of overweight and obesity in boys was higher than in girls and the ratio of overweight and obesity increased with age. Conclusion: The prevalence of overweight and obesity in 24-72 month children in Thai Nguyen is 15.4%; there was a significant difference between overweight and obesity among geography, gender and age.